2019
DOI: 10.1111/bjd.17832
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and prevalence of plaque psoriasis in patients with palmoplantar pustulosis

Abstract: Summary Background Palmoplantar pustulosis (PPP) is a chronic pustular skin condition on the palms and soles. The disease is often seen in combination with plaque psoriasis, and whether PPP is a variant of psoriasis has been debated. The disease prevalence of PPP and co‐occurring psoriasis is not yet established and the patient group remains understudied. Objectives To estimate the prevalence of PPP and co‐occurring psoriasis in three population‐based cohorts and to provide information on patient demographics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
35
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 17 publications
(40 reference statements)
3
35
3
Order By: Relevance
“…Notably, the AD diagnosis has been validated in children and adults with very high positive Columns may not sum to exactly 100% because of multiple therapy use predictive values in the Danish registries, thus ensuring that patients indeed had AD at the time of their referral [12]. A novel finding, however, is the somewhat low use of potent TCS, which could either be a sign of general undertreatment across therapies or due to steroid-phobia among patients [24]. Nonetheless, the low use of established AD therapies is in stark contrast to the high symptom burden and need for disease resolution that is reported among patients with AD [6,22].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the AD diagnosis has been validated in children and adults with very high positive Columns may not sum to exactly 100% because of multiple therapy use predictive values in the Danish registries, thus ensuring that patients indeed had AD at the time of their referral [12]. A novel finding, however, is the somewhat low use of potent TCS, which could either be a sign of general undertreatment across therapies or due to steroid-phobia among patients [24]. Nonetheless, the low use of established AD therapies is in stark contrast to the high symptom burden and need for disease resolution that is reported among patients with AD [6,22].…”
Section: Discussionmentioning
confidence: 99%
“…We found three national population‐based studies, based on claims data, estimating the annual prevalence of PPP, showing prevalence in Germany (2005), 15 Japan (2010–11) 7 and Korea (2015) 16 of 90, 120 and 52 cases per 100 000, respectively. In a recent multinational study, the annual PPP prevalences in the USA (2015–16), Denmark (2015–16) and Germany (2014) were estimated to be 9, 5 and 80 cases per 100 000, respectively 1 . Healthcare insurance claims data (USA and Germany) and data from the Danish NPR were used.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally PPP has been classified as a subgroup of psoriasis, as it is often seen in combination with psoriasis vulgaris. 1,2 Smoking, infection and certain drugs trigger or exacerbate the disease. 3 Many people who have PPP experience reduced quality of life, and one study reported that PPP is associated with greater impairment of quality of life than moderate-to-severe psoriasis.…”
mentioning
confidence: 99%
“…First, whether PPP represents a psoriasis variant remains a point of debate, 1,22–24 resulting in differences in the diagnosis of extrapalmoplantar lesions 3,19,25 . Second, among studies using registry data, the International Classification of Diseases codes used for PPP and PsV may differ or be missing 21,22 . Differences in data sources (from insurance data/free healthcare services) used by PPP studies might also influence the results 21 .…”
Section: Discussionmentioning
confidence: 99%